Self-Expanding Metal Stent (SEMS) Placement to Treat Bleeding from Late Radiation Esophagitis. (23rd January 2021) - Gill, Inayat; Antonios, Bana; Imam, Zaid; Ghaith, Gehad
Abstract : Radiation esophagitis is a serious complication occurring in patients receiving radiotherapy for head and neck cancers. Current treatment with proton pump inhibitors and mucosal protectants provides symptomatic relief with few studies showing improvement in erosive esophagitis or ulceration. Use of self-expandable metal stents (SEMS) in cases of erosive radiation esophagitis refractory to medical therapy has not been studied. We report a case of a patient presenting with recurrent hematemesis from late (chronic) radiation esophagitis with bleeding esophageal ulceration successfully treated with SEMS placement after failure of conservative medical management, proposing a possible utility for SEMS in this setting.